2021
DOI: 10.1061/(asce)gt.1943-5606.0002603
|View full text |Cite
|
Sign up to set email alerts
|

Role of Footing Embedment on Tunnel–Foundation Interaction

Abstract: This technical note investigates the effect of footing embedment depth on tunnel-structure interaction using geotechnical centrifuge testing. A two-story framed building on separate footings, either resting directly on the surface or embedded in the soil, and subjected to tunneling induced displacements is modeled.Measurements of the displacements of the footings and underlying soil, ground deformations, and structural distortions are presented. Results show that footing embedment increases foundation differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A parametri study was conducted to investigate the effects of main soil properties on the pile capacity loss caused by the excavation. The main conclusions can be summarized as follows: (1) The comparisons between the results from the proposed methods, well-documented field tests, centrifuge tests, and other analytical methods showed that the proposed approach was suitable for analyzing an uplift pile considering excavation effects. (2) The soil friction angle has a great influence on the pile uplift capacity loss caused by the excavation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A parametri study was conducted to investigate the effects of main soil properties on the pile capacity loss caused by the excavation. The main conclusions can be summarized as follows: (1) The comparisons between the results from the proposed methods, well-documented field tests, centrifuge tests, and other analytical methods showed that the proposed approach was suitable for analyzing an uplift pile considering excavation effects. (2) The soil friction angle has a great influence on the pile uplift capacity loss caused by the excavation.…”
Section: Discussionmentioning
confidence: 87%
“…With the development of urbanization around the world, the demand for extensive underground space utilization has increased dramatically in recent years. To meet these demands, deep excavations are widely used for the construction of geotechnical infrastructures such as tunnels [1], basements [2], bridge foundations [3], and launch shafts for piping [4]. Piles are often installed beneath these infrastructures to bear the uplift or compression loads.…”
Section: Introductionmentioning
confidence: 99%
“…Recent centrifuge (Xu et al, 2020(Xu et al, , 2021b and numerical/analytical modelling studies (Fu et al, 2018;Elkayam and Klar, 2019;Boldini et al, 2021) have demonstrated the need to consider the full structural details for framed buildings, for the accurate analysis of their response to tunnelling, highlighting, in particular, the important role of shear stiffness. Importantly, those studies primarily focused on buildings founded on the ground surface, whereas the role of embedded foundations or basements on tunnel-frame interaction has received much less attention (Xu et al, 2021a). In congested urban environments, it is common for buildings to have basements, which then alter their response to nearby tunnel construction when compared to equivalent buildings resting directly on the ground surface.…”
Section: Introductionmentioning
confidence: 99%